2014
DOI: 10.1038/bjc.2013.801
|View full text |Cite
|
Sign up to set email alerts
|

S0941: a phase 2 SWOG study of sorafenib and erlotinib in patients with advanced gallbladder carcinoma or cholangiocarcinoma

Abstract: Background:Gallbladder cancers and cholangiocarcinomas make up a heterogenous group of tumours with a poor prognosis in advanced stages. On the basis of evidence of dysregulation of the epidermal growth factor receptor, vascular endothelial growth factor and mitogen-activated protein kinase pathways in biliary cancers, we performed a phase 2 trial of sorafenib and erlotinib in patients with advanced biliary cancers.Methods:Eligible patients were previously untreated in the advanced setting with adequate hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 25 publications
1
70
0
Order By: Relevance
“…While early studies investigating novel agents targeting relevant signaling pathways demonstrated interesting antitumor activity in a small proportion of patients, the overall results have been disappointing, with outcomes largely similar to chemotherapy agents in the refractory setting ( Table 2) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). This may be in part due to the utilization of non-selected trials, where patients are eligible for enrollment regardless of their tumor genomic alterations.…”
Section: Targeted Therapies and The Role Of Cancer Genomics In Its Trmentioning
confidence: 99%
“…While early studies investigating novel agents targeting relevant signaling pathways demonstrated interesting antitumor activity in a small proportion of patients, the overall results have been disappointing, with outcomes largely similar to chemotherapy agents in the refractory setting ( Table 2) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). This may be in part due to the utilization of non-selected trials, where patients are eligible for enrollment regardless of their tumor genomic alterations.…”
Section: Targeted Therapies and The Role Of Cancer Genomics In Its Trmentioning
confidence: 99%
“…In adenocarcinoma of the biliary tract, overexpression of the epidermal growth factor receptor (EGFR) or the vascular endothelial growth factor receptor (VEGFR) have been found in approximately 27% and 59%, respectively (16). Clinical phase II trials of sorafenib (400 mg BID) or erlotinib (100 mg daily) in patients with advanced biliary cancer, however, failed to show a meaningful benefit (18). The addition of cetuximab to standard chemotherapy in the BINGO trial also failed to reveal benefit when compared to chemotherapy only (19).…”
Section: Discussionmentioning
confidence: 99%
“…Breakthroughs of immunologic therapies with antibodies targeting cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) and the programmed cell death protein 1 pathway (PD-1/PD-L1) have been made in a variety of malignancies [16][17][18][19][20][21]. Recent clinical trials of CCAs have focused on the agents targeted to specific genes such as EGFR and VEGFR, but promising clinical activity was not observed to date [22][23][24]. Further elucidation on tumor biology and molecular markers of CCAs is essential for future evaluation of targeted therapies.…”
Section: Discussionmentioning
confidence: 99%